VIOLENCE AGAINST PRIMARY HEALTH CARE PROFESSIONALS: A STUDY IN THE INTERIOR OF THE BRAZILIAN AMAZON - Beatriz Gomes Molinos; Elza Berger Salema Coelho; Rodrigo Otavio Moretti Pires; Sheila Rubia Lindner (Universidade Federal do Paraná, 2012)
This exploratory-descriptive study aimed to identify episodes of violence against health care professionals of the Family Health Strategy in the interior of the state of Amazonas and how these professionals perceive the conditions of security and prevention of violence at work. A self-applied semi-structured questionnaire was given, adapted from the Survey of Violence in the Workplace for Health Care Workers, in January of 2010. It was found that 10,1% of cases of violence were in the form of threats, 8,4% as provocation, 4,8% as intimidation and 5,7% as sexual harassment. The events were perpetrated against women. The health professionals did not consider their workplaces secure and 81.2% had not been trained to recognize or react in situations of violence. It is concluded that lack of awareness of the obligatory procedures, the fact of the topic not being discussed and staff not being warned about it may be the reason for the low incidence of violence in relation to the bibliography consulted.